Hybrid renewable energy integration (HREI) system for subtropical climate in Central Queensland, Australia. (October 2016) - Shafiullah, G.M.
Abstract: Global warming encourages interest worldwide to integrate large quantities of renewable energy into the power grid as these sources are free from greenhouse gas emissions as well as assisting to reduce the energy crisis. Demand for energy in the Capricornia region of Queensland, Australia is increasing due to expansion of the coal industry and the availability of nearby iconic tourist attractions such as the Great Barrier Reef. Therefore, to reduce the energy crisis as well as minimise global warming, a hybrid renewable energy integration system was developed to facilitate installation of significant renewable energy generation capacity into the grid in the subtropical climate of Central Queensland. The proposed hybrid renewable energy integration system comprises a prediction model that forecasts solar and wind generation in advance; a techno-economic model that analyses the techno-economic and environmental prospects of renewable energy; and a load management system by which utilities can manage customer load demand efficiently. It has been shown that a subtropical climatic region has significant potentialities for substantially increased use of renewable energy which can not only contribute to the reduction of global warming, but also reduce energy generation costs and help ameliorate the energy crisis. Highlights: Subtropical climatic regions have significant potential for both solar and wind energy generation. Prediction modeling assists utilities to manage grid operation by advising expected renewable generation in advance. Small-scale roof-top PV system is economically and environmentally viable and has a simple payback period of 4.4 years. Large-scale wind/PV/grid-connected system is economically and environmentally feasible and has a simple payback period of 7.8 years. Hybrid renewable energy integration system helps utilities to manage customer energy demand efficiently and effectively.